500 m speed skating performance analysis: focusing on 22/23 and 23/24 seasons - Song, J. H. (Korean Journal of Sport Biomechanics, 2025)
Objective: The purpose of this study is to analyze the performance of each continent and season based on the records of 500 m speed skating competitions. Method: To achieve this, the 500 m race records of 636 athletes from Group A who participated in 6 World Cups during the 2022-2023 and 2023-2024 seasons were collected and analyzed. Based on the official rankings and the speed records of 3 sections, analyses of correlation, coefficient of variation, and season difference by continent were conducted. Results: First, the starting section of the 0-100 m section for male athletes and the speed of the 100-500 m section for female athletes showed a high negative correlation with rankings. Second, in the analysis of the coefficient of variation by continent, the coefficient of variation in the 0-100 m section for male athletes increased in the 23/24 season for all continents. For female athletes, both North America and Asia decreased, and for European athletes, only the 0-100 m section increased. Third, significant differences were found in the 100-500 m section and the 0-500 m section in season-by-season differences. Finally, in the continental differences, there were significant differences in all sections for men. Conclusion: Based on the results of this study, it was possible to confirm performance differences that vary by continent and season.